A Novel Tripartite Evolutionary Game Model for Misinformation Propagation in Social Networks. (19th January 2022) - Li, Xianyong; Li, Qizhi; Du, Yajun; Fan, Yongquan; Chen, Xiaoliang; Shen, Fashan; Xu, Yunxia
Abstract : Misinformation has brought great challenges to the government and network media in social networks. To clarify the influences of behaviors of the network media, government, and netizen on misinformation propagation, a large number of influence parameters are proposed for the three participants. Then, a tripartite evolutionary game model for misinformation propagation is constructed. According to the proposed game model, the expected payoffs of three participants are analyzed when they adopt different strategies. The evolutionary stabilities of the game model are also analyzed theoretically. Finally, the impacts of different parameters on expected payoffs of three participants are analyzed experimentally. Meanwhile, coping strategies of three participants under different conditions are given. The experimental results show that the proposed tripartite evolutionary game model can properly describe the influence of network media, government, and netizen on misinformation propagation.